Question Number 104858 by ~blr237~ last updated on 24/Jul/20

  (1−a^3 )(1−b^3 )......(1−x^3 )(1−y^3 )(1−z^3 )        ????

Commented by1549442205PVT last updated on 24/Jul/20

what is your  question?

Answered by ~blr237~ last updated on 24/Jul/20

Just for laughing  : remember we usually  work we j=e^(i((2π)/3))   then  j^3 =1  And that product will be null

Commented by1549442205PVT last updated on 25/Jul/20

j=e^(i ((2π)/3)) =cos((2π)/3)+isin((2π)/3)⇒j^3 =(cos((2π)/3)+isin((2π)/3))^3   =cos2𝛑+isin2𝛑=1,of course,But you  don′t give this hypothesis in your  question.Nobody can guess your  thought